ANALISIS PENGARUH KREATIVITAS IKLAN, DAYA TARIK IKLAN DAN KREDIBILITAS ENDORSER TERHADAP BRAND ATTITUDE PADA PRODUK HANDPHONE ANDROID DI KOTA PEKANBARU - Marhadi '; Lilis Sulistyowati; Aida Nursanti (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This study aims to determine the influence of advertising creativity analysis,advertising appeal and credibility of endorser toward brand attitude on AndroidHandphone products in Pekanbaru. Inside The study consisted of a dependentvariable that brand attitude (Y), and three independent variables consisting ofadvertising creativity (X1), advertising appeal (X2), and Credibility of endorser(X3). Population of this study is the city of Pekanbaru with a sample of 300respondents aged 15-30 years with a criteria had watched ads AndroidHandphone. This study use a sampling technique that is purposive sampling andanalysis of research data using qualitative methods, quantitative and multipleregression equations with the help of SPSS (Statistic Services For Product andSolution.From these results obtained is advertising creativity, advertising appeal andcredibility of endorser on brand attitude of Androind Handphone product getsignificant effect in Pekanbaru city. This method of calculation models indicatethat advertising creativity, attractiveness and Credibility of endorser is able tomeet the forty-nine percents has influence on brand attitude and fifty-one percetsremaining are influenced by other factors.Keywords:Brand Attitude, Creativity inappeal,Credibility of Endorser.